The Correlation of Social, Political, and Economic Capital: A Study of Incumbent’s Capital ‎Utilization in the 2024 Legislative Elections - Ramadhani, Rahmah; Solihah, Ratnia; Witianti, Siti (Journal La Sociale, 2024)
This qualitative case study examines the strategic utilization of social, political, and economic capital ‎by Edi Sitorus, as an incumbent, in the 2024 legislative elections in Depok, Indonesia. The research ‎investigates how Sitorus effectively combines these forms of capital to enhance his electability and ‎secure electoral victories in a highly competitive environment. Data were collected through ‎interviews with the candidate, his campaign team, and some constituents, alongside observations of ‎campaign activities and analysis of relevant election documents. The findings reveal that Sitorus's ‎electoral success is significantly influenced by his adept use of social capital to engage with and ‎mobilize the community, political capital to exploit his incumbency advantages and party networks, ‎and economic capital to fund targeted campaign initiatives. This integrated approach not only ‎maximizes voter outreach but also aligns campaign strategies with the specific needs and ‎expectations of the electorate in Depok. The study underscores the importance of a synergistic use of ‎various capitals in legislative elections, highlighting their interdependent roles in building a ‎successful electoral strategy. By extracting into the dynamics of capital utilization in Indonesian ‎politics, this research contributes to a deeper understanding of electoral strategies and offers valuable ‎insights for candidates and political strategists in similar contexts.